Matematyka
Wercia777
2017-06-24 11:43:09
Porównaj liczby [latex](2 sqrt{2} ) ^{28} \ i \ ( frac{ sqrt{8} }{64} )^{-6} [/latex]
Odpowiedź
rastadream10
2017-06-24 15:05:01

[latex](2sqrt{2})^{28} =2^{28} cdot(2^frac{1}{2})^{28} = 2^{28}cdot2^{14}=2^{28+14} = 2^{42}\\(frac{sqrt{8}}{64})^{-6}=(frac{sqrt{2^{3}}}{2^{6}})^{-6} =( frac{2^{frac{3}{2}}}{2^{6}})^{-6} =(2^{frac{3}{2}-6})^{-6} = (2^{-frac{9}{2}})^{-6}=2^{27}[/latex] [latex]2^{42} extgreater 2^{27}\\(2sqrt{2})^{28} extgreater (frac{sqrt{8}}{64})^{-6}[/latex]

Asiap5200
2017-06-24 15:06:16

[latex](2 sqrt{2} )^2^8=(2^1*2^ frac{1}{2} )^2^8=(2^ frac{1}{1} *2^ frac{1}{2} )^2^8=(2^ frac{2}{2} *2^ frac{1}{2} )^2^8=(2^ frac{3}{2} )^2^8=2^ frac{3}{2} ^*^2^8=\=2^ frac{84}{2} =2^4^2\\ (frac{sqrt{8}}{64} )^-^6=( frac{ sqrt{2^3} }{2^6} )^-^6=( frac{2^3^*^ frac{1}{2} }{2^6} )^-^6=( frac{2^ frac{3}{2} }{2^6} )^-^6= (2^ frac{3}{2}^-^6)^-^6= (2^ frac{3}{2}^-^ frac{6}{1} )^-^6=\= (2^ frac{3}{2}^-^ frac{12}{2} )^-^6=(2^-^ frac{9}{2})^-^6=2^ frac{54}{2} =2^2^7[/latex] Z obliczeń wynika, że: [latex](2 sqrt{2} )^2^8 extgreater (frac{sqrt{8}}{64} )^-^6 [/latex]

Dodaj swoją odpowiedź